Trichoderma harzianum- and Methyl Jasmonate-Induced Resistance to Bipolaris sorokiniana Through Enhanced Phenylpropanoid Activities in Bread Wheat (Triticum aestivum L.) - Singh, Udai B.; Malviya, Deepti; Singh, Shailendra; Kumar, Manoj; Sahu, Pramod K.; Singh, H. V.; Kumar, Sunil; Roy, Manish; Imran, Mohd.; Rai, Jai P.; Sharma, A. K.; Saxena, A. K. (Frontiers in Microbiology, 2019)
The aim of the present study was to evaluate the impact of Trichoderma harzianum UBSTH-501- and methyl jasmonate-induced systemic resistance and their integration on the spot blotch pathogen, Bipolaris sorokiniana through enhanced phenylpropanoid activities in bread wheat (Triticum aestivum L.). It was found that the application of MeJA (>100 mg L-1) inhibits the germination of B. sorokiniana spores under controlled laboratory conditions. To assess the effect of MeJA (150 mg L-1) in combination with the biocontrol agent T. harzianum UBSTH-501 in vivo, a green house experiment was conducted. For this, biocontrol agent T. harzianum UBSTH-501 was applied as seed treatment, whereas MeJA (150 mg L-1) was applied 5 days prior to pathogen inoculation. Results indicated that application of MeJA (150 mg L-1) did not affect the root colonization of wheat by T. harzianum UBSTH-501 in the rhizosphere. The combined application of T. harzianum UBSTH-501 and MeJA also enhanced indole acetic acid production in the rhizosphere which in turn helps in plant growth and development. Further, the combined application found to enhance the activities of defense related enzymes viz. catalase, ascorbate peroxidase, phenylalanine ammonia lyase and peroxidase significantly in the plants under treatment which was further confirmed by assessing the transcript level of PAL and peroxidase genes using semi-quantitative PCR approach. The results showed manifold increase in salicylic acid (SA) along with enhanced accumulation of total free phenolics, ferulic acid, caffeic acid, coumaric acid, and chlorogenic acid in the leaves of the plants treated with the biocontrol agent alone or in combination with MeJA. A significant decrease in the disease severity and area under disease progress curve were also observed in the treatments with biocontrol agent and MeJA in combination as compared to B. sorokiniana alone treated plant. It was depicted from the results that PAL is the primary route for lignin production in wheat which reduce cellwall disruption and tissues disintegration and increase suberization and lignification of plant cell as seen by Scanning Electron microphotographs. These results clearly indicated that exogenous application of MeJA with T. harzianum inducing JA- and/or SA-dependent defense signaling increase the resistance in a cooperative manner.